Giovanni Boccaccio: Die verliebte Fiammetta Übersetzung von Johann Engelbert Noyse.Paralleldruck mit der Giolito-Ausgabe Venedig - Rubini Messerli, Luisa (Frühe Neuzeit, 2023)
Around 1600, two independent translations were made of Boccaccio's Elegia di madonna Fiammetta (ca. 1343/44) in the Upper German speech area. This historical critical edition presents the older of the two translations by Johann Engelbert Noyse. Its bilingual format allows the translation (Venice 1565) to be compared with the original Italian text. This edition is targeted at both a specialist audience and interested readers.